On the welfare cost of consumption fluctuations in the presence of memorable goods - Rong Hai; Dirk Krueger; Andrew Postlewaite (Quantitative Economics, 2020)
We propose a new category of consumption goods, memorable goods, that generate a utility flow even after physical consumption. Empirically, memorable goods expenditures exhibit frequent zero monthly purchases and lumpy expenditure spikes. Memorable goods expenditures are 20% the size of nondurable expenditures, but three times as volatile. We then develop a consumption-savings model with borrowing constraints and income risk that formalizes the notion of memorable goods and distinguishes them from other nondurable goods. We show that consumers optimally choose lumpy consumption of memorable goods. We then measure the welfare cost of consumption fluctuations using our calibrated model and empirically evaluate our calibrated model's predictions for the consumption response to predictable income changes. We find that the welfare cost of household-level consumption fluctuations induced by income shocks fall from 20.4 to 12.3 percentage points if memorable goods are accounted for, and that empirical estimates of excess sensitivity of consumption may significantly be driven by memorable goods expenditures.
Keywords: D91; E21; 330; Memorable goods; consumption volatility; welfare cost of incomerisk